The emergences of creative industry as a possible accelerator for economic development in Indonesia - Rahmanita, Nofi (Proceeding of International Conference on Art, Media, and Culture (ICAMAC), 2024)
This research aims to investigate the emergence of the creative industry as a possible accelerator for economic development within the framework of Indonesia's ongoing economic transformation. It addresses the concepts of the creative industry and the existing models of the creative economy. This research conducted a systematic literature review and PRISMA analysis to evaluate the data on the development of the creative industry and its role in the economic transition in Indonesia. Based on the data, the most significant emergences are as follows: 1) Ensuring access to financial resources; 2) Establishing an efficient educational system at all levels to assure the presence of trained labor and literate consumers of creative industry products; and 3) Ensuring the availability of a high-quality regulatory framework and infrastructure. In addition to this, recommendations for fostering the development of creative industries in transitioning economies are formulated with regards to the key stakeholders involved, such as the government, local authorities, universities, representatives from the creative industry, and other corporate entities. Keywords: creative industry, economic accelerator, economic development.